The Influence of Attitudes and Halal Perceptions on Intention to Visit Halal Tourism Destinations - Ramadhanti, Desna; Marsasi, Endy Gunanto (JESI (Jurnal Ekonomi Syariah Indonesia), 2023)
Tourism is a sector that is influenced by halal lifestyle trends. This study aims to analyze the effect of religiosity, subjective norms, halal perceptions, and attitudes on the intention to visit halal tourist destinations. The grand theory in this study is the Theory of Planned Behavior with Halal Perception as a novelty that describes consumer views on the application of sharia principles applied to tourist sites, as well as the availability of halal products and services in halal tourist destinations. The gap in this study is the attitude where there are differences in results in previous studies. This research utilizes a quantitative approach by distributing questionnaires to 221 respondents who are Muslims from the Islamic community and live in East Java. The research testing process is assisted by using the SEM-AMOS 24.0 program. This study shows that religiosity positively and significantly influences subjective norms, halal perceptions, and attitudes. Halal perceptions positively and significantly influence attitudes and purchase intentions. Attitude does not have a significant influence on purchase intention. This research intends to inspire and stimulate the creativity of business people in the tourism industry to realize a tourism business based on sharia principles.